Attention-deficit/hyperactivity disorder and driving - what should we be telling adolescents?. (24th May 2012) - Onugha, NN; Finlay, F
Abstract : Introduction: Motor vehicle accidents are the leading cause of death among teenagers in the UK, accounting for 30% of male deaths and 17% of female deaths. Factors increasing the vulnerability of young drivers include inattention, impulsivity, thrill-seeking tendencies, immature judgment, and impaired executive function skills. It is therefore unsurprising that young drivers with attention-deficit/hyperactivity disorder (ADHD) show increased risky-driving behaviour and motor vehicle accidents. The Driver and Vehicle licensing Agency (DVLA) lists ADHD as a medical condition that drivers must declare. As paediatricians, we see many adolescents with ADHD – what advice should we be giving them about driving? We decided to perform a literature review to explore this further so that we can advise our adolescent patients and their families. Methods: Searches of MEDLINE and EMBASE were carried out using the keywords 'ADHD', 'Driving', Adolescent' and 'Young people'. All studies identified as relevant were reviewed independently by two researchers. Results: Current data provides evidence of a relationship between ADHD and negative driving outcomes in adolescent ADHD drivers. The data is replicated in adult studies with 1 study reporting the simulated driving performance of sober, un-medicated adults with ADHD as impaired to a similar degree as alcohol-intoxicated adults without ADHD. Multiple studies report improved driving performance and a reduction in risky driving behaviours following the use of stimulant medication, mostly methylphenidate. A number of studies also suggest greater benefits from extended release medication over short acting preparations. Several studies look at the effects of distractions in teenage ADHD drivers. The presence of passengers, secondary tasks eg using a mobile phone, including those with a hands-free device, and reaching for objects in the car are all highlighted as increasing driving risk. Research also suggests that manual-drive vehicles result in safer driving practice than automatic. Conclusions: Paediatricians have the opportunity to reduce morbidity and mortality for both their adolescent ADHD drivers and the driving population at large. The literature provides evidence of possible counter-measures to reduce the identified risk factors. Discussions about safe driving behaviours should include parents, should start before driving age and should continue through all subsequent outpatient visits.